2015
DOI: 10.1098/rstb.2013.0278
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, marine regime shifts and the Soviet Union

Abstract: Regime shifts have been observed in marine ecosystems around the world, with climate and fishing suggested as major drivers of such shifts. The global and regional dynamics of the climate system have been studied in this context, and efforts to develop an analogous understanding of fishing activities are developing. Here, we investigate the timing of pelagic marine regime shifts in relation to the emergence of regional and global fishing activities of the Soviet Union. Our investigation of official catch stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Systems (i.e., sending, receiving, and spillover) are CHANS, integrated units in which humans and nature interact (Liu et al 2007a, b). In the FMFO telecoupling, Peru is the sending system, whereas receiving systems are nations that import FMFO, including China, the United States, Germany, Spain, Norway, and Denmark (Table 1, Chile, United States (FMFO); aquaculture and animal agriculture markets, global wheat market, Northern Humboldt Current System (money); Chile (knowledge); countries Peruvian travelers visit, economies they support (people); Glantz (1979), Barber and Chavez (1983), Orlic (2011), Fréon et al (2014 Flows (movements of material, information, people, etc., between systems) FMFO; money; knowledge (e.g., fishing vessel design, fish harvesting and processing, fishery sustainability strategies, military development strategies); people (e.g., Peruvian and foreign fishers, Peruvian students); Roemer (1970), Berrios and Blasier (1991), Orlic (2011), Fréon et al (2014, Österblom and Folke (2015) Agents (autonomous decision-making entites that directly or indirectly facilitate or hinder telecouplings)…”
Section: Systemsmentioning
confidence: 99%
“…Systems (i.e., sending, receiving, and spillover) are CHANS, integrated units in which humans and nature interact (Liu et al 2007a, b). In the FMFO telecoupling, Peru is the sending system, whereas receiving systems are nations that import FMFO, including China, the United States, Germany, Spain, Norway, and Denmark (Table 1, Chile, United States (FMFO); aquaculture and animal agriculture markets, global wheat market, Northern Humboldt Current System (money); Chile (knowledge); countries Peruvian travelers visit, economies they support (people); Glantz (1979), Barber and Chavez (1983), Orlic (2011), Fréon et al (2014 Flows (movements of material, information, people, etc., between systems) FMFO; money; knowledge (e.g., fishing vessel design, fish harvesting and processing, fishery sustainability strategies, military development strategies); people (e.g., Peruvian and foreign fishers, Peruvian students); Roemer (1970), Berrios and Blasier (1991), Orlic (2011), Fréon et al (2014, Österblom and Folke (2015) Agents (autonomous decision-making entites that directly or indirectly facilitate or hinder telecouplings)…”
Section: Systemsmentioning
confidence: 99%
“…However, research on the linkages and feedbacks among fisheries biota, habitats, and humans-indeed, the very identity of fisheries as coupled human and natural systems (CHANS) -is comparatively scarce, representing a hindrance to socially, ecologically robust fisheries management that achieves objectives set for fish and human stakeholders alike (Carlson et al, 2017b. To date, fisheries CHANS research has yielded insights for understanding social-ecological couplings at relatively large scales (e.g., national, global; Wilson, 2006;Pinsky and Fogarty, 2012;Österblom and Folke, 2015;Tapia-Lewin et al, 2017). Studies such as these lay a foundation for more comprehensive fisheries CHANS research that explicitly evaluates socialecological linkages at local to global scales.…”
Section: Introductionmentioning
confidence: 99%
“…Folke et al (2011) discussed how increasing global connections (e.g., integrated markets) requires reconnecting human development to the biosphere and a restructuring of institutions to address global challenges (e.g., shocks, feedbacks with a climate dimension due to land-use changes). Österblom and Folke (2015) demonstrated that the Soviet Union dramatically increased fishing in several distant water fisheries, which had profound ecological and socioeconomic effects on large marine ecosystems across the planet, such as regime shifts and responses from other nations including the establishment of fishing zones in coastal waters. While previous studies have made important scientific advances, more comprehensive research is needed to integrate various aspects of these and other distant cross-scale interactions for systematic assessment of drivers, patterns, processes, simultaneous socioeconomic and environmental interactions, feedbacks among different places, impacts beyond the focal systems, relationships among various distant linkages, and implications for governance and policy across the globe.…”
Section: Introductionmentioning
confidence: 99%